OC-081 Defining Cirrhosis with Fibroscan for entry to Hepatocellular Carcinoma Surveillance in Chronic Hepatitis C: a UK Cost Effectiveness Analysis. (4th June 2013) - Canavan, C; Corey, K; Hur, C
Abstract : Introduction: Chronic hepatitis C (HCV) is a significant risk factor for cirrhosis and subsequently hepatocellular carcinoma (HCC). HCV patients with cirrhosis are screened for HCC every 6 months. Surveillance for progression to cirrhosis, and consequently access to HCC screening, is not standardised. Liver biopsy, the usual test to determine cirrhosis, carries a risk of significant morbidity. Ultrasound elastography (Fibroscan) is a non-invasive test for cirrhosis. This study assesses the cost effectiveness of annual surveillance for cirrhosis in chronic HCV and the effect of replacing biopsy with fibroscan to diagnose cirrhosis. Methods: A Markov decision analytic model simulated a hypothetical cohort of 10000 patients with chronic HCV initially without fibrosis over their lifetime. Cirrhosis surveillance strategies assessed were: (A) no surveillance; (B) current practise; (C) fibroscan in current practise with biopsy to confirm cirrhosis; (D) fibroscan completely replacing biopsy in current practise (definitive); (E) annual biopsy; (F) annual fibroscan with biopsy to confirm cirrhosis; (G) annual definitive fibroscan. Results: The model was calibrated with good visual fit. Annual definitive fibroscan is the optimal strategy choice. Sensitivity analysis shows this outcome to be robust. The cost-effective frontier holds strategies A and G with E dominated by extension. All other strategies are strictly dominated. It diagnoses 20% more cirrhosis than the current strategy, with 549 extra patients per 10000 accessing screening over a lifetime; consequently 76 additional HCCs are diagnosed. Lifetime cost is an additional £98.78 per patient compared to current strategy for an additional 1.72 unadjusted life years. Annual fibroscan surveillance of 132 patients diagnoses one additional HCC over a lifetime. The ICER for annual definitive fibroscan is £6557.06/QALY gained. Conclusion: Annual definitive fibroscan may be a cost-effective surveillance strategy to identify cirrhosis in patients with chronic HCV to allow access to HCC screening. Disclosure of Interest: None Declared